2020
DOI: 10.1039/d0ra01066a
|View full text |Cite
|
Sign up to set email alerts
|

The construction of fluorophoric thiazolo-[2,3-b]quinazolinone derivatives: a multicomponent domino synthetic approach

Abstract: A library of unique fluorophoric thiazolo[2,3-b]quinazolinones were synthesized under acid catalyzed one pot microwave irradiation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Taking our previously reported results into consideration, 22 we attempted analogous one pot three component cascade reaction of equimolar mixture of 2-amino thiazole 1, aryl aldehydes 2a-h and cyclic-1,3-dicarbonyls 3a-b under acid mediated microwave heating at 150 °C in a microwave synthesizer. Here also, unexpected formation of a series of compound 5 was achieved in spite of compound 4 ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking our previously reported results into consideration, 22 we attempted analogous one pot three component cascade reaction of equimolar mixture of 2-amino thiazole 1, aryl aldehydes 2a-h and cyclic-1,3-dicarbonyls 3a-b under acid mediated microwave heating at 150 °C in a microwave synthesizer. Here also, unexpected formation of a series of compound 5 was achieved in spite of compound 4 ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ) was also synthesized by previously reported procedure. 22 Fluorescence spectra of benzothiazoloquinazolinone (II) were then measured upon addition of 5 equivalents various metal ions. From the fluorescence spectra, it was observed that no such significant change in emission intensities at 395 nm was occurred after addition of the metal ions (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cooling then poured in ice-water with stirring followed by filtration of the solid product and watching thoroughly with cold water many times to remove the excess of acids , drying then recrystallized from water (Table 1) Method B ( Mohanta, Pati & Behera, 2020): Equimolar (0.001 mole) of thioamide , dimidone and substituted benzaldehyde were mixed and irradiated under microwave oven at power (700 watt) for (1 min) in presence of (2 % mole)boric acid and (2 drops ) glacial acetic acid. Cooling followed by adding (10ml) of acetone to separate the boric acid then filtration and reduce the filtrate volume to a half by evaporation followed by adding of ice-water with stirring to afford the solid product which then filtrated off, dry followed by recrystallized form water.…”
Section: Methodsmentioning
confidence: 99%
“…A series of thirty-four fluorophoric thiazolo- [2, 3-b] quinazolinone derivatives (5aa, 5ab, …., 5bq) ( Fig. S6 ) was synthesized and characterized by Mohanta et al, (2020) (21). All the ligands were drawn in Chemdraw Ultra 8.0 and were converted into 3D MDL Mol format by using chem3D Ultra 8.0.…”
Section: Modeling Of Fluorophoric Thiazolo-[23-b] Quinazolinone Derimentioning
confidence: 99%